Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1093/humupd/dmh053
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free fetal DNA in maternal blood: kinetics, source and structure

Abstract: The kinetics and structure of cell-free fetal DNA in maternal plasma is currently under investigation. Plasma fetal DNA seems quite stable albeit cleared rapidly following birth, suggesting continuous fetal DNA release into the maternal circulation during pregnancy. However, to understand better the kinetics of circulating DNA, studies to determine the biological (structural) form in which fetal and maternal DNA exist and the mechanisms underlying variation in plasma are warranted to ensure quantitative diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 97 publications
(85 reference statements)
2
114
0
8
Order By: Relevance
“…The release of cffDNA is a physiological process present in all mammals, but its possible roles and implications in normal pregnancy (and more importantly parturition) remain poorly understood. Placental growth involves proliferation, differentiation and syncytial fusion of cytotrophoblasts, which is associated with significant release (grams per day) of microvesicles-encapsulated, cffDNA-containing apoptotic trophoblasts content into maternal circulation (Nelson 1996, Huppertz et al 1998, Huppertz & Kingdom 2004, Bischoff et al 2005, Taglauer et al 2014. These microparticles, also referred to as syncytiotrophoblast microvesicles (SCTMs), were first described more than 100 years ago in lung capillaries of women who died from preeclampsia (Schmorl 1893) and were later described as a feature of normal pregnancy, although increased in preeclampsia (Johansen et al 1999).…”
Section: Cell-free Dnamentioning
confidence: 99%
“…The release of cffDNA is a physiological process present in all mammals, but its possible roles and implications in normal pregnancy (and more importantly parturition) remain poorly understood. Placental growth involves proliferation, differentiation and syncytial fusion of cytotrophoblasts, which is associated with significant release (grams per day) of microvesicles-encapsulated, cffDNA-containing apoptotic trophoblasts content into maternal circulation (Nelson 1996, Huppertz et al 1998, Huppertz & Kingdom 2004, Bischoff et al 2005, Taglauer et al 2014. These microparticles, also referred to as syncytiotrophoblast microvesicles (SCTMs), were first described more than 100 years ago in lung capillaries of women who died from preeclampsia (Schmorl 1893) and were later described as a feature of normal pregnancy, although increased in preeclampsia (Johansen et al 1999).…”
Section: Cell-free Dnamentioning
confidence: 99%
“…It is also possible for the absolute quantity to actually change in opposition to relative abundance. Recently, we reported that particles from maternal plasma, which may be derived from apoptotic cells, stained positive for acridine orange (AO), a nucleic acid dye (Bischoff et al, 2004). We sorted the AO+ apoptotic bodies and PCR amplified male specific Y sequences, demonstrating that they contain male fetal DNA (Bischoff et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that particles from maternal plasma, which may be derived from apoptotic cells, stained positive for acridine orange (AO), a nucleic acid dye (Bischoff et al, 2004). We sorted the AO+ apoptotic bodies and PCR amplified male specific Y sequences, demonstrating that they contain male fetal DNA (Bischoff et al, 2004). For such analysis of subcellular apoptotic bodies, accurate quantitation is needed to determine the optimum amount of staining reagent required.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only one out of eight treated children is a CAH-affected girl. Even with early foetal sex typing, using PCR amplification of cell-free foetal DNA in maternal blood, performed during the first trimester (13)(14)(15), the ethical dilemma remains that healthy foetuses (seven out of eight versus three out of eight) will be treated for a short period of time for the sake of benefit of others.…”
Section: Introductionmentioning
confidence: 99%